Uncertain futures: Imaginaries, narratives, and calculative technologies - Jens Beckert; Richard Bronk (Max Planck Institute for the Study of Societies, 2019)
Dynamic capitalist economies are characterised by relentless innovation and novelty and hence exhibit an indeterminacy that cannot be reduced to measurable risk. How then do economic actors form expectations and decide how to act despite this uncertainty? This paper focuses on the role played by imaginaries, narratives, and calculative technologies, and argues that the market impact of shared calculation devices, social narratives, and contingent imaginaries underlines the rationale for a new form of 'narrative economics' and a theory of fictional (rather than rational) expectations. When expectations cannot be anchored in objective probability functions, the future belongs to those with the market, political, or rhetorical power to make their models or stories count. The paper also explores the dangers of analytical monocultures and the discourse of best practice in conditions of uncertainty, and considers the link between uncertainty and some aspects of populism. – – Kapitalistische Ökonomien sind durch unablässige Neuerung gekennzeichnet. Innovationen zeigen eine Unbestimmtheit, die nicht auf meßbares Risiko reduziert werden kann. Wie bilden Akteure in der Wirtschaft Erwartungen und legen ihre Handlungen im Angesicht dieser Ungewissheit fest? Der Beitrag befasst sich mit der Rolle von Vorstellungen, Narrativen und kalkulativen Techniken in der Wirtschaft und zeigt, dass die Bedeutung verwendeter kalkulativer Instrumente, sozial geteilter Narrative und kontingenter Vorstellungen eine neue Form "narrativer Wirtschaftswissenschaft" und einer Theorie fiktionaler (anstelle von rationalen) Erwartungen notwendig macht. Wenn Erwartungen nicht in objektiven Wahrscheinlichkeitsfunktionen verankert werden können, gehört die Zukunft denjenigen, die über die marktliche, politische oder rhetorische Macht verfügen, ihren Erzählungen Geltung zu verschaffen. Der Beitrag befasst sich im letzten Teil mit den Gefahren analytischer Monokulturen und dem Diskurs zu "best practices" in durch Ungewissheit gekennzeichneten Situationen und leitet daraus einige Schlussfolgerungen für das Verständnis von Populismus ab.
hdl:21.11116/0000-0005-78CC-F
Keywords: 300; calculation; fictional expectations; future; imaginaries; innovation; narrative economics; uncertainty; fiktionale Erwartungen; Innovation; Kalkulation; narrative Wirtschaftswissenschaften; Ungewissheit; Vorstellungen; Zukunft